Understanding Kompangan As Jambi-Malay Traditional Arts and Cultural Heritage: An Anthropological Research - Haidar, Abdullah; Herindar, Evania; Chairiyati, Fauziah (Universitas Islam Negeri Sunan Kalijaga, 2023)
Like other traditional art forms, Kompangan in Jambi Seberang faces challenges in the preservation and transmission of culture due to globalization and changes in social patterns. Despite its cultural significance, research on the strategies used by local groups to maintain and promote this community is limited. The research gap includes the lack of detailed studies of the role of certain community groups, such as the Ulu Gedong, in preserving Kompangan and the mechanisms of cultural transmission within these groups. This research aims to fill these gaps by delving deeper into the history of Kompangan as a musical instrument and the roles of the Ulu Gendong Group in preserving the Kompangan as a traditional Malay art in Jambi Seberang. By using anthropological research, the results of this study indicate that Kompangan art is part of Malay Islamic culture and traditional musicals of Jambi Province, especially from Jambi Seberang. Immigrants from the Middle East have brought Kompangan. Sambilan Group was founded in Kampung Tengah, Jambi, and that is where Kompangan got its start. Kompangan art has evolved in several districts, including Ulu Gedong. Ulu Gedong, Riyatul Jannah, Riyatul Abedin, and Al-Hidayah are the four main Kompangan. The young generation plays a crucial role in preserving Kompang in Jambi Seberang. The goal for the next generation is to value their culture more and keep their cultural legacy alive, particularly this Kompangan art.